Estudo de nanopartículas de Pt/C modificados com Sn, Ru e Ta para células a combustível de álcool direto - Queiroz, Maria Aparecida Ribeiro (2020)
In this work, the influence of the addition of Sn, Ru and/or Ta on the electrocatalytic activity of Pt/C electrocatalysts, synthesized by the thermal decomposition method of polymeric precursors, was studied. Chemical-physical characterization, the measur